Concentração inibitória mínima de fármacos de primeira e segunda linha do Mycobacterium tuberculosis multirresistente e mutações relacionadas à isoniazida e rifampicina em laboratório de referência de Minas Gerais, Brasil - Alan Douglas Gonçalves (2015)
Tuberculosis is a disease of global importance and represents a serious public health problem involving social and economic aspects for Brazil and the world. The emergence of drug resistance in Mycobacterium tuberculosis is a growing concern and increased incidence of multidrug-resistant and extensively drug-resistant TB complicates treatment and disease control. The simple separation of clinical isolates of M. tuberculosis as "resistant" based on sensitivity testing the "critical concentration" must be supplemented by quantitative measures tests to demonstrate the existence of different levels of resistance, in order to better assess drugs available to conduct a proper treatment in multidrug-resistant and extensively drug-resistant tuberculosis. The minimal inhibitory concentration is the lowest concentration that inhibits bacterial growth, a quantitative measure of drug resistance. The study of mutations in genes which confer resistance to drugs have been described as important in the evaluations of resistance levels. Thus, this study aimed to evaluate the minimal inhibitory concentration of the first and second line drugs and mutations related to isoniazid and rifampicin of clinical isolates of multidrug-resistant M. tuberculosis in reference laboratory of the state of Minas Gerais. A total of 115 strains of multidrug-resistant M. tuberculosis corresponding to 97 patients were analyzed at the Central Public Health Laboratory of the State of Minas Gerais, Ezequiel Dias Foundation, between 2008 and 2011. The minimal inhibitory concentration was determined by the automated method BACTEC® MGIT® 960. The drugs tested and their concentration ranges are: isoniazid (0.007 to 32 g/mL), rifampicin (0.007 to 64 g/mL), streptomycin (0.06 to 64 g/mL), ethambutol (0.12 to 64 g/mL), amikacin (0.06 to 32 g/mL), levofloxacin (0.03 to 64 g/mL), rifabutin (0.007 to 16 g/mL) and cycloserine (0.25 to 128 g/mL). We also promoted the molecular detection of mutations in rpoB regions, katG and inhA through Genotype MTBDRplus test. Of multidrug-resistant strains of M. tuberculosis that period who met the inclusion criteria, 42 were evaluated for the minimal inhibitory concentration (MIC), three of these, extensively drug-resistant. As for the molecular detection of mutations were 40 strains evaluated. Forty percent (40%) of the strains showed low level resistance to isoniazid, 13.5% to rifampicin, 31.2% to streptomycin, 33.3% for ethambutol and levofloxacin and 38.9% for rifabutin. Regarding cycloserine, all strains showed MIC <32 mg / mL and 100% (n = 2) of multirreistente strains resistant to amikacin showed a high level of resistance. Concerning the mutations in the rpoB and rifampicin resistance levels, the D516V mutation was associated with low level resistance to rifampicin. This mutation was also associated with strains sensitive to rifabutin. The S531L mutation in rpoB was associated with low levels of rifabutin resistance while the H526Y mutation was associated with high level. With respect to mutations in katG and inhA, katG S315T mutation was associated with a moderate level of resistance to isoniazid, while simultaneous mutations S315T katG and C15T inhA were associated with high level. Knowledge of resistance levels to drugs of first and second line of M. tuberculosis and extensively drug-resistant mutirresitente and detection of related mutations may provide important information to assist in conducting the treatment for these patients.